Analysis of Divorce Problems Outside the Court According to Hadith and Compilation of Islamic Law: Analisis Masalah Perceraian di Luar Pengadilan Menurut Hadits dan Kompilasi Hukum Islam - Nur Rofiq; Ema Marhumah; Rahmawati; Orien Effendi; Nurul Aeni (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The ideal hope for a household is the realization of a happy, harmonious and peaceful family. It's just that this often doesn't materialize because of a family problem and dispute that is difficult to compromise on, so the path taken is divorce (talak). The problem that will be examined is the validity of divorce outside the courtroom in the perspective of hadith. This article will contain an explanation of the problems of divorce with the formulation of important issues; first, what is the law on divorce?, and second, how is the hadith about divorce understood in the Indonesian context? To answer this question, the writer uses descriptive-analytical theory. After the required data has been collected, the authors carry out an analysis and comparison with positive law through the Compilation of Islamic Law. As a result, divorce is indeed something that is permitted by religion and at the same time becomes behavior that is hated by Allah. So it takes policy and comprehensive understanding of this problem. On the other hand, the state requires that the divorce process be carried out in the Religious Courts, in order to ensure the benefit of each party and become a standard legal basis.